The Evolving Face of Nuclear Proliferation: A Challenge to Global and Regional Security - Quilop, Raymund Jose G. (Philippine Political Science Journal, 2009)
The issue of nuclear proliferation involves both states and non-state actors. This essay, however, goes beyond examining the issue in relation to states, their motivations for producing or acquiring these weapons, how possession of nuclear weapons impact on the relations of certain states, and other related issues. Instead, it focuses on another aspect of nuclear proliferation: the possibility of non-state actors, specifically terrorists, having access to fissile materials and related technology. It argues that the risk of non-state actors having access to nuclear material and technology increases as the demand for nuclear energy as a viable alternative source of energy by states intensifies. This problem is compounded by the presence of black markets, where nuclear materials and technology are clandestinely sold and bought.